THE INFLUENCE OF AUDIO VISUAL MEDIA ON STUDENT LEARNING OUTCOMES IN SCIENCE SUBJECTS AT SDIT DARUL ABROR - Dini Rusmiati; Ani Siti Anisah; Ade Holis (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The purpose of this research is to find out how much influence the use of audio-visual media has on student learning outcomes in science subjects. Media is considered as one of the most important things in the learning process. The importance of media can help teachers in teaching and learning activities, making it easier for a teacher to convey his message to students. The use of learning media makes it easier for students to receive and understand messages or material conveyed by educators to them. The method used in this research is a descriptive quantitative method in which the research process uses statistics to analyze data by describing the results that have been collected. Based on the results of the data analysis, it can be concluded that for the validity test, there are 10 valid statement items on variable (X) and 10 valid statement items on variable (X). The variable reliability test (X) shows a reliability coefficient value of 0.79 and the variable reliability test (Y) shows a reliability coefficient value of 0.83. The reliability test is categorized as very high. The student's responses to a variable (X) showed a percentage of 83.36% in a very good category and student responses to a variable (Y) showed a percentage of 89.14% in a very good category. While the results of the hypothesis test showed that the proposed hypothesis can be accepted with a Tcount value that is greater than the Ttable value, namely 7.169 > 2.056. After going through several previous calculation stages, it can be concluded that the use of audio-visual media has an effect on student learning outcomes in science subjects with a percentage value of 66.40% with outside influences of 33.60%.